2017
DOI: 10.14814/phy2.13175
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia‐induced proliferation of HeLa cells depends on epidermal growth factor receptor‐mediated arginase II induction

Abstract: Solid tumors can often be hypoxic in regions, and cancer cells can respond to hypoxia with an increase in proliferation and a decrease in apoptosis, leading to a net increase in viable cell numbers. We have recently found that in an osteosarcoma cell line, hypoxia‐induced proliferation depends on arginase II induction. Epidermal growth factor receptor (EGFR) has been shown to mediate the hypoxia‐induced cellular proliferation in some cancer cell lines. We hypothesized that hypoxia‐induced proliferation of HeLa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 23 publications
3
8
0
Order By: Relevance
“…These finding are consistent with our previous studies (Setty et al. ) in HeLa cells and supports the concept of a hypoxia responsive EGF‐EGFR pathway in endothelial cells leading to arginase II expression. It has been described that endothelial release of various growth factors, including EGF, can activate epidermal cells in the lung to promote lung development.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These finding are consistent with our previous studies (Setty et al. ) in HeLa cells and supports the concept of a hypoxia responsive EGF‐EGFR pathway in endothelial cells leading to arginase II expression. It has been described that endothelial release of various growth factors, including EGF, can activate epidermal cells in the lung to promote lung development.…”
Section: Discussionsupporting
confidence: 93%
“…We have previously shown that exposing HeLa cells to 1% oxygen resulted in a ~20‐fold increase in EGF mRNA and a substantial increase in pEGFR protein levels (Setty et al. ). Our results demonstrate that hypoxia also leads to a substantial increase in EGF expression and subsequent EGFR activation in hPMVEC.…”
Section: Discussionmentioning
confidence: 99%
“…conditions (4% O 2 ) (67-69). Our findings correspond to observations made by others with HeLa cells, in that oxidative radicals have been observed at significant levels during normoxic culture (70); in contrast, hypoxia relieves oxidative stress and increases the viability of HeLa cells (71). In this regard, physiological oxygen tensions in the majority of human tissues range from 0 to 5% O 2 ; for example, vaginal oxygen tension is typically 1-2% O 2 , rising briefly to 5% O 2 during sexual stimulation (72); a similar range has been observed for cervical and uterine oxygen tension (73).…”
Section: Physiological Oxygen Tension Permits Physiological Concentrasupporting
confidence: 93%
“…To identify the molecular mechanism underlying cell growth in cervical cancer promoted by ATXN1, we analyzed the relevant regulatory signaling pathways. EGF induces cell growth in human cancer cells [ 19 ] and activates the Akt and ERK signaling pathways [ 31 , 32 ]. Considering this, we hypothesized that ATXN1 is involved in EGF-mediated cancer growth.…”
Section: Resultsmentioning
confidence: 99%
“…EGF is a 6-kDa polypeptide that elicits a number of biological responses, including profound alterations in cellular growth and differentiation, in a variety of normal and tumoral cell types [ 18 , 19 ]. EGF induces cell proliferation by binding to the prototype transmembrane tyrosine kinase receptors 1 and 2, resulting in the phosphorylation of several protein components.…”
Section: Introductionmentioning
confidence: 99%